FACIT-Fatigue scale in patients with cold agglutinin disease: psychometric validation and estimation of clinically meaningful change - Cella, David; Hill, Quentin A.; Karaouni, Alia; Joly, Florence; Sourdille, Timothee; Shafer, Frank; Wardęcki, Marek; Kosinski, Mark; Röth, Alexander (Frontiers in Hematology, 2025)
PurposeTo validate the use of Functional Assessment of Chronic Illness Therapy-Fatigue (FACIT-Fatigue) questionnaire in cold agglutinin disease (CAD) patients using qualitative and quantitative methods and to estimate meaningful within-patient change (MWPC).MethodsQualitative assessment used outcomes from a survey among CAD patients and their caregivers in US. Quantitative assessment used outcomes from two Phase-3 trials in CAD wherein fatigue was evaluated as a key secondary endpoint using the FACIT-Fatigue questionnaire. The reliability, validity, and responsiveness of the FACIT-Fatigue questionnaire were assessed. MWPC was estimated using anchor-based (mean change, receiver operating characteristic [ROC] curves, and logistic regression) and distribution-based methods.ResultsQualitative analyses (n=16) showed that fatigue was the most common and bothersome symptom. All patients reported that FACIT-Fatigue questionnaire captured their experiences of CAD-related fatigue. Quantitative analysis included 55 patients from both studies. Items of FACIT-Fatigue scale were internally consistent (Cronbach’s alpha coefficient: 0.94 at baseline; 0.96 at Week 26). Generally, correlations showed good convergent validity (>0.40). The MWPC estimates ranged from 2.0 to 15.7. Based on more robust ROC and regression-based methods, IQR of MWPC estimates was 4.1–7.3, and individual responder definitions were in range of 5–8 points, where “5” is the lowest recommended MWPC threshold for FACIT-Fatigue in CAD.ConclusionFACIT-Fatigue is a reliable, valid, responsive scale in CAD. The MWPC estimates for FACIT-Fatigue in patients with CAD were consistent with other disease estimates published previously, and “5” can be considered as the lowest recommended threshold for meaningful clinical response in patients with CAD.